2016
DOI: 10.1007/s11165-015-9504-8
|View full text |Cite
|
Sign up to set email alerts
|

Confidence in the Knowledge Base of English Language Learners Studying Science: Using Agency to Compensate for the Lack of Adequate Linguistic Identity

Abstract: Confidence in the knowledge base of English language learners studying science: using agency to compensate for the lack of adequate linguistic identity. AbstractChanges in the cultural and linguistic environments of learners are often associated with identity shifts. The aim of this study was to explore what identity shifts occur when science students from Bahraini national schools transition to an international university. The role of two aspects of learner identity -that is, English proficiency and science b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…A TIMSS analysis study concluded that when students are motivated to learn, it will have a positive effect on their academic results [24]. A student's motivation is influenced by their beliefs, interests, and attitudes, which can have either a positive or negative impact [26].…”
Section: Student Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A TIMSS analysis study concluded that when students are motivated to learn, it will have a positive effect on their academic results [24]. A student's motivation is influenced by their beliefs, interests, and attitudes, which can have either a positive or negative impact [26].…”
Section: Student Factorsmentioning
confidence: 99%
“…Liking learning is referred to as the students' desire to learn, which could be defined as motivation [66]. Students' motivation influences their beliefs, interest, and attitudes [26], which could result in a positive effect on student attainment. Students will learn better when they believe that subjects will benefit them, when they are interested in classroom activities, and when they have a positive attitude to learning in school.…”
Section: Student Factors That Have An Impact On Science and Math Achi...mentioning
confidence: 99%
“…At present, China emphasizes traditional cultural education, aiming to consolidate the cultural foundation and enhance cultural confidence. To strengthen cultural exchanges between countries, it is necessary to give full play to the role of the English language to accurately and meticulously display the profound cultural connotations of China and to realize the collision of values and exchanges of consciousness among different cultures [8]. Integrating Chinese traditional culture education in English teaching in colleges and universities is of great significance for correcting the subordinate status of English communication tools, strengthening the cultural comparison between English and Chinese in the same content area, promoting the spirit of patriotism, and correctly viewing the differences between cultures of different countries [9].…”
Section: Introductionmentioning
confidence: 99%
“…In Bezug auf WhatsApp-Kommunikation in Schulklassen haben sich innerhalb der Erziehungswissenschaft unterschiedliche Forschungsfelder etabliert. Einerseits werden Gruppenchats und die Auswirkungen auf Sprachkompetenz untersucht (Gimranova, Nurmanova, und CohenMiller 2017;Hayes und Mansour 2017;Keogh 2017;u.a. Avci und Adiguzel 2017).…”
Section: Introductionunclassified